PRELIMINARY INVESTIGATIONS ON A RECENTLY DISCOVERED COPPER MINERALIZATION IN THE LYCIAN NAPPES, SW TURKEY - Akbulut, Mehmet; Pişkin, Özkan (Ofioliti, 2024)
This study reports preliminary textural, mineralogical and bulk-rock chemical data on a newly discovered copper mineralization in SW Turkey. The sampled 3 meter length outcrop includes pieces of a chalcopyrite + sphalerite + pyrite bearing massive and tabular ore vein oriented sub-parallel to the foliation planes of the sheared micro-grained dolerite host. The continuation of the ore vein is unknown. Fragments of radiolarian chert locally acting as foot-wall to the ore are also found along the foliation planes. The micro-grained dolerite is mainly sterile; however, the radiolarian chert is locally impregnated by chalcopyrite. The mineralization appears to be a fragmented distal section of an ophiolite-hosted volcanogenic massive sulphide (VMS) deposit emplaced during obduction of the ocean-floor units. More field, mineralogical and chemical data are needed to evaluate the mineralization and to find the main massive sulphide lens.